Review Artikel: Keanekaragaman Berbagai Jenis Gulma di Perkebunan Kelapa Sawit - Leo Nainggolan, Zames Jhon (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
Oil palm (Elaeis guineensis Jacq.) is a strategic plantation commodity in Indonesia that plays an important role in the national economy. One of the main obstacles in oil palm cultivation, both in the phase of unproductive crops (TBM) and productive plants (TM), is the growth of weeds. Weeds compete directly with major crops in absorbing water, nutrients, and sunlight, and can inhibit vegetative growth and productivity of fresh fruit bunches (FFB). This study aims to identify weed diversity based on morphology and life cycle in oil palm TBM and TM land. The method used is a descriptive-narrative literature review with reference sources from scientific journals in 2013–2024. The results of the study showed that broadleaf weeds such as Ageratum conyzoides and Chromolaena odorata were dominant in both phases. Annual weeds dominate TBM land, while in TM there are variations of broadleaf, grass, teki-tekian, and pakuan weeds. This information is important to design a specific, efficient, and environmentally friendly weed control strategy in oil palm plantation management.